The main concern of burn survivors in Iran - Vahid Zamanzadeh; Lila Valizadeh; Mojgan Lotfi; Feridoon Salehi; Assef Khalili (Wolters Kluwer Medknow Publications, 2016)
Background: The present work was conducted to study the burn patients' experiences to get an insight into their main concerns when they suffer the tragic event, recover from it, and adjust back in the society, so that better rehabilitation programs can be planned corresponding to their needs as well as to the needs of the society and the existing situations. Materials and Methods: In this qualitative study, 17 burn survivors were enrolled. Unstructured interviews were used for data collection. All the interviews were recorded, transcribed, and analyzed using qualitative content analysis method. Results: Based on the existing elements of the explicit textual meanings, two categories of threat and disturbance were formed. The category of "threat" was extracted from the following five subcategories: (a) Threat to physical life; (b) threat to the process of living; (c) psychological threat; (d) spiritual threat; and (e) social threat. The category of "disturbance" was extracted from the following three subcategories: (a) Sensory disturbance: Suffering pain; (b) self-concept disturbance; and (c) behavioral disturbance. Conclusions: Burn survivors experience severe pain, enduring and suffering in their daily activities after burn. Passing through these difficult trajectories is perceived as a threat and disturbance in self-integrity.